2009
DOI: 10.1002/humu.20960
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of three splicing mutations identified in the PMM2 gene: Toward a new therapy for congenital disorder of glycosylation type Ia

Abstract: The congenital disorders of glycosylation (CDG) are a group of diseases caused by genetic defects affecting N-glycosylation. The most prevalent form of CDG-type Ia-is caused by defects in the PMM2 gene. This work reports the study of two new nucleotide changes (c.256-1G>C and c.640-9T>G) identified in the PMM2 gene in CDG1a patients, and of a previously described deep intronic nucleotide change in intron 7 (c.640-15479C>T). Cell-based splicing assays strongly suggest that all these are disease-causing splicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 38 publications
(44 reference statements)
0
47
1
1
Order By: Relevance
“…A large variety of mutations have been identified in our Iberian cohort of unrelated PMM2-CDG patients: 25 (83%) are missense mutations (Briones et al 2002;Quelhas et al 2007), four of them newly reported here (p.Y102C, p.T118S, p.P184T, and p.D209G); one nonsense (p.R123X) (Briones et al 2002), three affecting the splicing of mRNA (IVS3+ 2T>C; IVS3-1G>C and IVS7-9T>C) (Briones et al 2002;Vega et al 2009), and a deletion mediated by an Alu retrotransposition displaying the complete loss of exon 8 (Schollen et al 2007a). Of these 30 identified mutations, 13 have only been reported in our series of patients.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…A large variety of mutations have been identified in our Iberian cohort of unrelated PMM2-CDG patients: 25 (83%) are missense mutations (Briones et al 2002;Quelhas et al 2007), four of them newly reported here (p.Y102C, p.T118S, p.P184T, and p.D209G); one nonsense (p.R123X) (Briones et al 2002), three affecting the splicing of mRNA (IVS3+ 2T>C; IVS3-1G>C and IVS7-9T>C) (Briones et al 2002;Vega et al 2009), and a deletion mediated by an Alu retrotransposition displaying the complete loss of exon 8 (Schollen et al 2007a). Of these 30 identified mutations, 13 have only been reported in our series of patients.…”
Section: Resultsmentioning
confidence: 77%
“…The primers used for cDNA and gDNA amplifications were designed using the ENSEMBL database (http://www. ensembl.org/index.html; ENSG00000140650) and GenBank accession number NM_000303.2 as described in Vega et al 2009. Amplifications of exons and flanking intronic sequences were performed using the FastStart kit (Roche Applied Sciences, Indianapolis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once regarded as junk DNA, intronic and intergenic sequences are now perceived to contain crucial splicing machinery elements and other gene expression regulating motifs. Recently, several studies have shown that mutations disturbing these important elements can lead to disease [34][35][36][37]. Therefore, we expect that high throughput sequencing of the entire 3.3 Mb candidate region might reveal a more complex mutation associated with DLB in family DR246.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme converts mannose-6-phosphate to mannose 1-phosphate and is a key enzyme in the generation of N-linked glycans. An intronic mutation in the PMM2 gene was shown to provoke the exonization of 123 bp of intronic sequence, which was successfully reverted with SSO (Vega et al, 2009). Other pseudoexons activated by mutations have also been described in different glycosylation defects such as TMEM165 deficiency (MIM 614727), affecting a protein located mainly in the Golgi compartment and involved in calcium and pH homeostasis necessary for correct processing of glycan chains (Foulquier et al, 2012).…”
Section: Enzyme Defects With Multisystemic Phenotypesmentioning
confidence: 99%